Significance of the magnetic resonance imaging while planning surgery of intramedullary spinal cord tumors - E. I. Slyn'ko; Ya. S. Babiy; A. V. Muravsky; V. V. Verbov; O. Yu. Chuvashova; R. B. Kostrytsya (Ukrainian Neurosurgical Journal, 2006)
MRI-diagnosis were retrospectively analyzed in 154 patients with intramedullary spinal cord tumors. The contrast enhancement was utilized in 36 (23%) of them. The detailed neuroradiological analysis allowed to minimized risk of intraoperative spine damage and could provide the prognosis of the future patient recovery.Analysis of the magnetic-resonance imaging while intramedullary tumors resection planning must provide information concerning exact location of the tumor, relationship with cord, characteristics of the cyst, the precisely tumor borders, intra-extra axial tumor growing, and the histological diagnosis.